Theory of Planned Behavior on The Implementation of Environmental Management Accounting - Kedisan, Anak Agung Vidyaswari; Ratnadi, Ni Made Dwi; Putri, I Gusti Ayu Made Asri Dwija; Mimba, Ni Putu Sri Harta; Sisdyani, Eka Ardhani (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 18 No 1 (2023)DO - 10.24843/JIAB.2023.v18.i01.p08, 2023)
G20 2022 put some emphasis on recent environmental issues; one of them is that water pollution that may cause by not only the large company but also micro, small and medium enterprise (MSME) waste, especially textiles, the most found in Denpasar City. This study examines the influence of attitude toward behaviour (ATT), subjective norm (SN) and perceived behavioural control (PBC) on the intention and then the implementation of environmental management accounting (EMA) using legitimacy theory and theory of planned behaviour (TPB). The results showed that ATT and PBC positively influenced the intention to EMA, while SN did not. PBC influence the implementation of EMA positively, while the intention did not. This research enriches legitimacy theory and TPB by revealing the two theories not being able to fully predict the implementation of EMA due to the geographical area, lack of political interest and government regulations that still need improvement. Keywords: attitude toward behavior, subjective norm, perceived behavioral control, environmental management accounting